Reliability of transient elastography for the diagnosis of advanced fibrosis in chronic hepatitis C. Issue 9 (30th April 2008) - Arena, U; Vizzutti, F; Abraldes, J G; Corti, G; Stasi, C; Moscarella, S; Milani, S; Lorefice, E; Petrarca, A; Romanelli, R G; Laffi, G; Bosch, J; et al.
Abstract : Background: Transient elastography (TE) has received increasing attention as a means to evaluate disease progression in patients with chronic liver disease. Aim: To assess the value of TE for predicting the stage of fibrosis. Methods: Liver biopsy and TE were performed in 150 consecutive patients with chronic hepatitis C-related hepatitis (92 men and 58 women, age 50.6 (SD 12.5) years on the same day. Necro-inflammatory activity and the degree of steatosis at biopsy were also evaluated. Results: The areas under the curve for the prediction of significant fibrosis (⩾F2), advanced fibrosis (⩾F3) or cirrhosis were 0.91, 0.99 and 0.98, respectively. Calculation of multilevel likelihood ratios showed that values of TE <6 or ⩾12, <9 or ⩾12, and <12 or ⩾18, clearly indicated the absence or presence of significant fibrosis, advanced fibrosis, and cirrhosis, respectively. Intermediate values could not be reliably associated with the absence or presence of the target condition. The presence of inflammation significantly affected TE measurements in patients who did not have cirrhosis (p<0.0001), even after adjusting for the stage of fibrosis. Importantly, TE measurements were not influenced by the degree of steatosis. Conclusions: TE is more suitable for the identification of patients with advanced fibrosis than of those with cirrhosis or significant fibrosis. In patients in whom likelihood ratios are not optimal and do not provide a reliable indication of the disease stage, liver biopsy should be considered when clinically indicated. Necro-inflammatory activity, but not steatosis, strongly and independently influences TE measurement in patients who do not have cirrhosis.